2020
DOI: 10.1093/jxb/eraa030
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanisms of callose priming in mycorrhiza-induced resistance

Abstract: Mycorrhizal plants display enhanced resistance to several pathogens. However, the molecular mechanisms regulating mycorrhiza-induced resistance (MIR) are still elusive. We aim to study the mechanisms underlying MIR against Botrytis cinerea and the role of callose accumulation during this process. Mycorrhizal tomato plants inoculated with Rhizoglomus irregularis displayed callose priming upon B. cinerea infection. The callose inhibitor 2-deoxy-d-glucose abolished MIR, confirming the relevance of callose in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 73 publications
2
68
1
Order By: Relevance
“…I3CA treatment increased ABA levels, which activates a starch amylase (BAM1) to trigger augmented callose deposition against P. cucumerina [ 37 ]. A similar role of ABA and starch metabolism has also been reported in mycorrhiza-induced callose priming in tomato plants upon infection by necrotrophic fungal pathogen B. cinerea [ 24 ]. Intriguingly, ABA can enhance or repress Flg22-induced callose deposition in Arabidopsis depending on growth conditions [ 35 ] ( Figure 1 A).…”
Section: Regulation Of Defense-related Callose Depositionsupporting
confidence: 63%
See 2 more Smart Citations
“…I3CA treatment increased ABA levels, which activates a starch amylase (BAM1) to trigger augmented callose deposition against P. cucumerina [ 37 ]. A similar role of ABA and starch metabolism has also been reported in mycorrhiza-induced callose priming in tomato plants upon infection by necrotrophic fungal pathogen B. cinerea [ 24 ]. Intriguingly, ABA can enhance or repress Flg22-induced callose deposition in Arabidopsis depending on growth conditions [ 35 ] ( Figure 1 A).…”
Section: Regulation Of Defense-related Callose Depositionsupporting
confidence: 63%
“…Furthermore, resistance-inducing chemicals including salicylic acid (SA), SA analog benzo(1,2,3) thiadiazole-7-carbothioic acid S-methyl ester (BTH), and the nonprotein amino acid BABA can augment depositions of pathogen-inducible callose [ 21 , 22 ]. It has also been recently reported that in tomato and wheat callose priming can be induced by Rhizophaus irregularis , a mycorrhizal fungus that can enhance resistance to several pathogens such as the necrotrophic fungal pathogen Botrytis cinerea in tomato [ 23 , 24 ].…”
Section: Defense-related Callose Deposition In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we also found a potential PGPB interaction gene, ERF9, which is an ethylene response factor that negatively regulates plant defense (Huang 2016). In addition, the pair of co-regulated genes ATMIN7 and GSL05 are also related with the plant immune response (Deslandes 2012 andSanmartín 2020). Another important finding is the pair of co-expressed genes AL6 and UBP14, which are involved in the phosphate starvation response (Chandrika 2013 and.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus was cultivated in potato dextrose agar plates, supplemented with freeze‐dried tomato leaves. Three weeks later, B. cinerea spores were collected from plates in 0.5X potato dextrose broth as previously described (Sanmartín et al, 2020).…”
Section: Methodsmentioning
confidence: 99%